2008
DOI: 10.1093/jxb/ern048
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of carotenoid biosynthetic genes expression and carotenoid accumulation in the green alga Haematococcus pluvialis under nutrient stress conditions

Abstract: Haematococcus pluvialis, a green alga, accumulates carotenoids, predominantly astaxanthin, when exposed to stress conditions. In the present work, changes in the pigment profile and expression of carotenogenic genes under various nutrient stress conditions and their regulation were studied. Nutrient stress and higher light intensity in combination with NaCl/sodium acetate (SA) enhanced total carotenoid and total astaxanthin content to 32.0 and 24.5 mg g(-1) of dry biomass, respectively. Expression of carotenog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
1
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(88 citation statements)
references
References 27 publications
3
74
1
10
Order By: Relevance
“…They also induced astaxanthin synthesis independent of de novo protein synthesis (Kobayashi et al 1993, Steinbrenner andLinden 2001), suggesting ROS mediate stress response and carotenogenesis in H. pluvialis at a post-translational level (Steinbrenner and Linden 2003). Unlike PDS and CrtR-b, however, treatment with various transcriptional and translational inhibitors suggested that BKT gene expression was dependent on de novo protein synthesis (Vidhyavathi et al 2008). Considering PDS is shown to be located in the chloroplast, whereas BKT activity is found in the cytosolic LBs, this discrepancy can be explained by the distinct subcellular localization of individual carotenoid biosynthetic enzymes.…”
Section: +mentioning
confidence: 98%
“…They also induced astaxanthin synthesis independent of de novo protein synthesis (Kobayashi et al 1993, Steinbrenner andLinden 2001), suggesting ROS mediate stress response and carotenogenesis in H. pluvialis at a post-translational level (Steinbrenner and Linden 2003). Unlike PDS and CrtR-b, however, treatment with various transcriptional and translational inhibitors suggested that BKT gene expression was dependent on de novo protein synthesis (Vidhyavathi et al 2008). Considering PDS is shown to be located in the chloroplast, whereas BKT activity is found in the cytosolic LBs, this discrepancy can be explained by the distinct subcellular localization of individual carotenoid biosynthetic enzymes.…”
Section: +mentioning
confidence: 98%
“…However, under stress conditions, β(beta)-carotene is converted into astaxanthin primarily via echinenone, canthaxanthin, and phoenicoxanthin, being β(beta)-carotene and echinenone substrates of BKT, while canthaxanthin and phoenicoxanthin are the substrates of CHY. In this way, astaxanthin accumulates as a secondary carotenoid under stress conditions [ 98 ]. Further introduction of fatty acids to the hydroxyl groups by esterifi cation leads to the production of mono-and di-esterifi ed astaxanthin in H. pluvialis [ 93 ].…”
Section: Astaxanthin Biosynthesis In X Dendrorhous and In Other Orgamentioning
confidence: 99%
“…Ha. pluvialis produces astaxanthin that protects the photosynthetic apparatus from photo-oxidative damage (under high light intensities) or nutrient stresses (Vidhyavathi et al, 2008). HtS showed that members of the Ulvophyceae, Chlorophyceae, Charophyceae, Prasinophyceae, Zygnemophyceae, Bacillariophyceae and Chrysophyceae were also present, but they may have been dormant and thus not observed in culture.…”
Section: Active Variables Supplementary Variablesmentioning
confidence: 99%